Modeling of Fuel Cell Cold Start and Dimension Reduction Simplification Method. Issue 4 (11th February 2020) - Jiang, Hongliang; Xu, Liangfei; Struchtrup, Henning; Li, Jianqiu; Gan, Quanquan; Xu, Xin; Hu, Zunyan; Ouyang, Minggao
Abstract : Sub-zero startup ability remains a key barrier for commercial application of polymer electrolyte fuel cells (PEMFC), especially for automotive applications. In order to improve the startup ability and durability of fuel cells, understanding of the characteristics and mechanisms of cold start is essential, and here modeling of fuel cell cold start plays an important role. In this study, a one-dimensional model is developed to simulate the fuel cell cold start. The model includes mass transport and phase change, heat transfer and electrochemical reaction. Key features such as membrane water and local current distributions are analyzed. Based on the one-dimensional model and simulation results, a spatial reduced simplified model is developed that distinguished only n states across the cell. The simplified model inherits the key features of the one-dimensional model, while the computational cost is significantly reduced to 10% (from 216 s to 20.88 s). The one-dimensional model and simplified model are both validated by the cold start experiment and the voltage error and temperature error are within 15% and 1.2 K respectively. Thus, the proposed simplified model could be used in dynamic simulation and in further multi-scale modeling study to build a stack model.